Forest growing stock volume of the northern hemisphere: Spatially explicit estimates for 2010 derived from Envisat ASAR - Santoro, Maurizio; Beaudoin, André; Beer, Christian; Cartus, Oliver; Fransson, Johan E.S.; Hall, Ronald J.; Pathe, Carsten; Schmullius, Christiane; Schepaschenko, Dmitry; Shvidenko, Anatoly; Thurner, Martin; Wegmüller, Urs (Remote sensing of environment, 2015)
This paper presents and assesses spatially explicit estimates of forest growing stock volume (GSV) of the northern hemisphere (north of 10°N) from hyper-temporal observations of Envisat Advanced Synthetic Aperture Radar (ASAR) backscattered intensity using the BIOMASAR algorithm. Approximately 70,000 ASAR images at a pixel size of 0.01° were used to estimate GSV representative for the year 2010. The spatial distribution of the GSV across four ecological zones (polar, boreal, temperate, subtropical) was well captured by the ASAR-based estimates. The uncertainty of the retrieved GSV was smallest in boreal and temperate forest (<30% for approximately 80% of the forest area) and largest in subtropical forest. ASAR-derived GSV averages at the level of administrative units were mostly in agreement with inventory-derived estimates. Underestimation occurred in regions of very high GSV (>300m3/ha) and fragmented forest landscapes. For the major forested countries within the study region, the relative RMSE between ASAR-derived GSV averages at provincial level and corresponding values from National Forest Inventory was between 12% and 45% (average: 29%). •Wall-to-wall estimates of forest growing stock volume (GSV) north of 10°N•Spatial distribution of GSV well reproduced in four biomes•Percent error of ASAR-derived GSV averages at provincial level: between 12% and 45%.•Underestimation for areas with GSV>300m3/ha and in fragmented forest landscapes